Cadaver Study of the Morphometry of the Ovary in Bangladeshi Women - Perven, Hosna Ara; Nurunnabi, Abu Sadat Mohammad; Ara, Shamim; Siddiqua, Dilruba (Anwer Khan Modern Medical College Journal, 2012)
Title corrected from 'Cadaver Study if...' to Cadaver Study of...' on 04/02/2013. Ovarian morphological parameters e.g. length, breadth and thickness, may be affected by patients' age, laterality of the organ and presence of systemic disease. The present study was aimed to see the morphometric difference of ovaries in relation to age in Bangladeshi women and compare with previous local and foreign studies. This is a Cross-sectional descriptive type of study done in the department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2009. The study was performed on 140 post mortem human ovaries collected from 70 unclaimed female dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into three agegroups including group A (10-13 years), group B (14-45 years) & group C (46-52 years) and the length, breadth and thickness of the ovaries were measured by using a slide calipers and recorded. The difference in mean length, breadth and thickness between the right ovary and the left ovary was statistically significant in all age group. The differences were also significant between group A & group B, group A & group C and group B & group C. DOI: http://dx.doi.org/10.3329/akmmcj.v3i2.11689 AKMMC J 2012: 3(2): 19-22